Menguatkan Keluwesan dan Kebaruan Berpikir Kreatif Siswa Sekolah Dasar Melalui Project-Based Learning (PjBl) yang Kontekstual: keterampilan berpikir kreatif - Kastur, Annita; hidayati, fitria; Kurniasari, Kurniasari; Julianto, Julianto; Rahmawati, Endah (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2025)
Creative thinking is an essential skill for addressing the challenges of 21st-century learning, especially in science subjects such as Natural Sciences (IPA). The purpose of this study is to identify the obstacles faced by elementary school students in developing creative thinking skills when understanding basic science concepts, through the perspectives of both teachers and students, and to offer alternative solutions in the form of applicable learning approaches. This research employed a descriptive qualitative method, with data collected through student creative thinking questionnaires, observation sheets, and semi-structured interviews in three public elementary schools: SDN Lakarsantri I, SDN Lakarsantri II, and SDN Lidah Wetan IV. The participants included fifth-grade students and their homeroom teachers. The results indicate that students’ creative thinking abilities in science learning are generally in the medium to low category, particularly in the indicators of flexibility and originality. Therefore, improving creative thinking in elementary science learning requires comprehensive changes, including enhancing students’ self-confidence, strengthening teacher competencies, and creating a supportive learning environment that encourages experimentation, flexible thinking, and the expression of original ideas. Active, exploratory, and constructive learning approaches must be implemented to foster deeper, more meaningful, and applicable mastery of science concepts. Based on the findings, the researcher recommends a contextually designed Project-Based Learning (PjBL) model as a potential solution to enhance students’ flexibility and originality in thinking. PjBL is deemed suitable as it allows students to independently, flexibly, and creatively solve real-world problems.